Apple leaves and their major secondary metabolite phlorizin exhibit distinct neuroprotective activities: evidence from in vivo and in silico studies - El-Hawary, Seham; Hammam, Walaa. E.; El-Mahdy El-Tantawi, Mona; Yassin, Nemat A. Z.; Kirollos, Farid N.; Abdelhameed, Mohamed F.; Abdelfattah, Mohamed A. O.; Wink, Michael; Sobeh, Mansour (Arabian journal of chemistry, 2021)
Apple, Malus domestica Borkh., a fruit-producing and medicinal plant, is reported to have a wide array of biological effects including a neuroprotective potential. In this work, the phytochemical composition of the leaf extract from M. domestica was thoroughly investigated using LC-MS/MS. Phlorizin, the major secondary metabolite was also isolated and characterized using MS and NMR data. Total phenolic content (TPC) and the total flavonoid content (TFC) were determined. The in vivo neuroprotective effect of the extract and its major component phlorizin was evaluated in rats using the novel object recognition (NOR) test. The antioxidant activity of the extract and phlorizin was evaluated in vitro by the well-known DPPH assay and in vivo through determining the total antioxidant capacity (TAC), and some oxidative stress parameters such as the reduced and oxidized glutathione (GSH, GSSG) respectively and the lipid peroxidation marker (MDA) in rats previously treated with dexamethasone (10 mg/kg i.p.) daily for 9 days and the tropane alkaloid scopolamine (1 mg/kg. i.p.) for 2 consecutive days (day 7 and 8). Moreover, the extract and phlorizin were tested to block the activity of β-secretase (BACE1) that is involved in the formation of amyloid-β (Aβ) plaques in silico and in vivo, an important player in the pathogenesis of Alzheimer’s disease. Molecular docking was performed to confirm the potential of phlorizin and other individual components of the extract to bind to and block BACE1. The extract and phlorizin revealed substantial antioxidant potential with IC50 of 6.93 and 5.14 µg/mL, respectively in DPPH assay. They were able to significantly restore TAC, increase GSH, and reduce both GSSG and MDA levels in the dexamethasone/scopolamine treated rats. Both extract and phlorizin were able to inhibit BACE1 with IC50 of 1.65 and 1.18 µg/mL, respectively. Our results provide evidence that M. domestica and its major secondary metabolite phlorizin are promising neuroprotective natural agents for treating Alzheimer Disease and other neurodegenerative disorders especially recognition impairment disorders. More studies are needed to elaborate the mechanism of action.